Analyzing percussive technology from the Earlier Stone Age archaeological record - Caruana, Matthew V. (My University, 2015)
Percussive technology plays an integral in role lithic tool production and thus has had a significant impact on the evolution of the archaeological record. The characteristic damage patterns that result from percussive activities preserve a record of hominin behaviour, although there remains no comprehensive method for analyzing them. In fact, percussive tools have been largely overlooked in archaeological research, which has obscured their behavioural insights. Recent interests in the commonalities of percussive tool use within the Primate Order have suggested that investigating the evolutionary continuity of these tools may provide a window into the origins of lithic technology. This research presents a framework of analytical techniques for the study of hammerstones from the Earlier Stone Age record. As stone-knapping activities remain the focus of archaeological research, understanding how the use of hammerstones has changed throughout time is a critical concern. A ‘focal lens’ approach is developed to facilitate inter-assemblage comparisons that can be used to construct an evolutionary perspective on the use of these tools. Implications for raw materials, selection behaviours and comparative research are developed to test the potential for future directions in the study of percussive technology.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy. April, 2015
Keywords: Stone age.; Tools, Prehistoric.; Technology and civilization.